Functional physiological phenotyping and transcriptome analysis provide new insight into strawberry growth and water consumption - Jiang, Lili; Sun, Ting; Wang, Xiaofang; Zong, Xiaojuan; Wu, Chong (Frontiers in Plant Science, 2022)
Global warming is expected to increase global agricultural water scarcity; thus, optimized irrigation schedules are important and timely for crop production. Deficit irrigation, which balances crop growth and water consumption, has been proposed, but the critical threshold is not quantitively determined. Here, we conducted experiments of progressive drought and water recovery of strawberry depending on the high-throughput physiological phenotyping system “Plantarray”. The critical soil water content (θcri) below which plant transpiration significantly decreases is obtained from the inflection point of the transpiration rate (Tr) - volumetric soil water content (VWC) curve fitted by a piecewise function. The physiological traits of water recovery under genetically dependent θcri and severe drought, i.e., WR_θcri and WR_SD, were compared to those under well irrigation (CK). The results showed that the midday Tr and daily E and plant growth of WR_θcri were slightly lower or close to those of CK during the progressive drought and water recovery phases, but those of WR_SD were significantly lower than those of CK during water stress and did not recover after rehydration. To detect the molecular mechanism underlying progressive drought and water recovery, transcriptome analysis of samples obtained 12 h before and 12 h and 36 h after water recovery in the WR_θcri, WR_SD, and CK treatments was conducted. GO terms and KEGG pathways indicated that mineral absorption and flavonoid biosynthesis contributed largely to the reversible influence of drought stress in the WR_θcri treatment. Therefore, physiological phenotyping and transcriptome data both supported that irrigation at the θcri will reduce water consumption without sacrificing plant growth, which provides a potential, quantitative, and balanceable water-saving strategy for strawberry irrigation and other agricultural crops.